Knowledge, Attitude, and Practice of Academic Students about STIs and HIV/AIDS at the University of Fianarantsoa: A Cross-Sectional Study - Andriamamonjisoa, Andriamizaka Johary; Rakotomalala, Radovololona; Andriananja, Volatiana; Raberahona, Mihaja; Randriamampionona, Faramalala; Andrianasolo, Radonirina Lazasoa; Randria, Mamy Jean de Dieu; Rakotoarivelo, Rivonirina Andry (European Scientific Journal, ESJ, 2023)
Introduction: Sexually transmitted infections (STIs) facilitate and increase the risk of HIV transmission. This paper focuses on evaluating the knowledge, attitude, and practice of academic students about sexually transmitted infections and HIV at the university of Fianarantsoa. Materials: An analytical cross-sectional study was conducted among the students at the Andrainjato University. Knowledge was assessed using a score of one point for each correct answer. Results: 1035 students were included and 67.7% (n=701) had good knowledge about STIs and HIV/AIDS. The sexual transmission (83.9%; n=868) was the most commonly known. On multivariate analysis, being a student at the faculty of medicine (p<0.001, aOR 137.3 [19.1-988]), faculty of Letters (p<0.001, aOR 4.5 [2.8-7.2)]), or the Normal Graduate School (NGS) (p<0.001, aOR 6.7 [3.3-13.7]), being tested for HIV before (p= 0.002, aOR 1.6 [1.2-2.2]), constituted the major factor of good knowledge about sexual infections. Majority (71.8%, n=743) have had sexual intercourse before, and the median age of their first sexual activities was 18 years (17-20). The use of Condom (44.4%, n=460) was the most practiced STIs prevention method. This is followed by fidelity (19.8%; n=205) and abstinence (11.4%, n=118). Among the students, 29.3% (302) had high-risk sexual behavior during the last three months. Conclusion: The proportion of academic students with good knowledge of STIs and HIV was not satisfying. There was also discordance between the knowledge of STIs prevention and the daily university practice of the students.